IMPLEMENTATION OF ELECTRONIC PERFORMANCE (E-PERFORMANCE) IN INCREASING WORK ACCOUNTABILITY OF BKD EMPLOYEES IN SIDOARJO REGENCY - Pratiwi, Nirmala Anggun Dwi; Choiriyah , Ilmi Usrotin (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: The purpose of this study is to examine how the Regional Civil Service Agency (BKD) of Sidoarjo Regency has increased the accountability of civil servants through the use of the Electronic Performance System (E-Kinerja). The background of this research is the transition from a manual performance appraisal system to a digital system, which is expected to improve employee discipline in achieving performance targets and increase transparency and efficiency. Method: qualitative with a descriptive approach through in-depth interviews, observations, and documentation with employees and managers of the e-Performance application at BKD Sidoarjo. Results:  shows that the implementation of e-Performance. Indicators of effective communication, adequate resources, positive employee disposition, and a clear bureaucratic structure. This system has proven to be effective in motivating employees, especially through its integration with the Employee Income Allowance (TPP), and has succeeded in encouraging the creation of a transparent and accountable work culture. Novelty: this research lies in the emphasis that the application of e-Performance does not only function as an administrative instrument, but also as a means to build a work culture that is oriented towards results and accountability in the local government environment.